The Influence of Parasite Infections on Host Immunity to Co-infection With Other Pathogens - Mabbott, Neil A. (Frontiers in Immunology, 2018)
Parasites have evolved a wide range of mechanisms that they use to evade or manipulate the host's immune response and establish infection. The majority of the in vivo studies that have investigated these host-parasite interactions have been undertaken in experimental animals, especially rodents, which were housed and maintained to a high microbiological status. However, in the field situation it is increasingly apparent that pathogen co-infections within the same host are a common occurrence. For example, chronic infection with pathogens including malarial parasites, soil-transmitted helminths, Mycobacterium tuberculosis and viruses such as HIV may affect a third of the human population of some developing countries. Increasing evidence shows that co-infection with these pathogens may alter susceptibility to other important pathogens, and/or influence vaccine efficacy through their effects on host immune responsiveness. Co-infection with certain pathogens may also hinder accurate disease diagnosis. This review summarizes our current understanding of how the host's immune response to infection with different types of parasites can influence susceptibility to infection with other pathogenic microorganisms. A greater understanding of how infectious disease susceptibility and pathogenesis can be influenced by parasite co-infections will enhance disease diagnosis and the design of novel vaccines or therapeutics to more effectively control the spread of infectious diseases.